Tugas Perkembangan pada Anak Akhir - Nurul Azizah Kurniawati; Solehuddin Solehuddin; Ilfiandra Ilfiandra (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2019)
The task of development is a task that must be completed properly by each individual. The task of development is always in the individual life phase. The task of development that should be priorized is the task of the development of the final child because in it contains the discovery of his identity so that it will affect adolescence and adelt life later. Based on the search for various sources, it is known that the developmental tasks are so many depending on the psychological figures that make it and are influenced by environmental factors. The results of this study can be used ad a reference for parents, teachers, and further research.